Sexual Taboo Reflected In Ayu Utami`S Saman Novel (1998): A Feminist Perspective - Wulandari, Fitriya Dessi, Dr. Phil. Dewi Candraningrum, M.Ed, Nur Hidayat, M.Pd (2014)
This study is strived to reveal sexual taboo which is reflected in Ayu Utami`s SAMAN (1998) novel. SAMAN (1998) novel is analyzed by using feminist perspective. The analysis is done by determining three objects: the first is describing social background of Indonesia in twentieth century, the second is analyzing the novel based on the structural elements, and the third is analyzing the issue based on feminist perspective. This research is a descriptive qualitative research. There are two types of data sources. The primary data data sources is Ayu Utami`s SAMAN (1998) novel translated by Pamela Allen. The secondary data sources are books, journals, and internet sources related to the study. The two kinds of data collected through library research and analyzed with descriptive analysis. Based on the research, the researcher pulls the following conclusions. First, the structural element of the novel described the character and characterization, setting of time and place, plot, point of view, and theme. All of them are correlated to each other forming unity. Second, based on feminist perspective, sexual taboo was revealed with other descriptions of women`s participation, women`s right, women`s role and women`s position reflected in Ayu Utami`s SAMAN (1998) novel.